Observation of Λb0 → Λc+ D̄(*)0 K- and Λb0 → Λc+ Ds*- decays - Aaij, Roel; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; Kubat, Jakub; et al. (The European physical journal. C, Particles and fields, 2024)
The decays Lambda(0)(b) -> Lambda(+)(c) (D) over bar (()*()0) K- and Lambda(0)(b) -> Lambda(+)(c) D-s*(-) are observed for the first time, in proton-proton collision data at root s = 13TeV, corresponding to an integrated luminosity of 5.4fb(-1) collected with the LHCb detector. Their ratios of branching fractions with respect to the Lambda(0)(b) -> Lambda(+)(c) D-s(-) mode are measured to be B(Lambda(0)(b) -> Lambda(+)(c) (D) over bar (0) K-)/B(Lambda(0)(b) -> Lambda(+)(c) D-s(-)) = 0.1908(-0.0034-0.0018)(+0.0036+0.0016) +/- 0.0038, B(Lambda(0)(b) -> Lambda(+)(c) (D) over bar*(0) K-)/B(Lambda(0)(b) -> Lambda(+)(c) D-s(-)) = 0.589(-0.017-0.018)(+0.018+0.017) +/- 0.012, B(Lambda(0)(b) -> Lambda(+)(c) D-s*(-))/B(Lambda(0)(b) -> Lambda(+)(c) D-s(-)) = 1.668 +/- 0.022(-0.055)(+0.061), where the first uncertainties are statistical, the second systematic, and the third, for the Lambda(0)(b) -> Lambda(+)(c) (D) over bar (()*()0) K- decays, are due to the uncertainties on the branching fractions of the D-s(-) -> K- K+ pi(-) and (D) over bar0 -> K+ pi(-) decay modes. The measured branching fractions probe factorization assumptions in effective theories and provide the normalization for future pentaquark searches in Lambda(0)(b) -> Lambda(+)(c) (D) over bar (()*()0) K- decay channels.
Im Titel sind 0, +, (*) und - hochgestellt, b, c und s sind tiefgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, S. Skuza, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov und 1073 weitere
Online veröffentlicht: 5. Juni 2024
Gesehen am 17.09.2025